Analysis of Purity and Uncertainty for 1, 2, 3, 4-Tetrachlorobenzene with the Mass Balance Method - MA Kang; YANG Ran; WANG Hai-feng; HE Ya-juan; LIU Fei (Yankuang ceshi, 2013)
A traceable method is presented, to study the purities of certified reference material of 1,2,3,4-tetrachlorobenzene with the assessment of uncertainties. The purities of 1,2,3,4-tetrachlorobenzene were determined by the mass balance method. The qualitative analysis of main non-volatile impurities was identified as 1,2,3,5-tetrachlorobenzene with Gas Chromatography-Mass Spectrometry (GC-MS) and standard addition. The quantitative analysis for the impurities was measured by Gas Chromatography-Flame Ionization Detector (GC-FID). The content of water and ash in 1,2,3,4-tetrachlorobenzene were respectively measured by Karl-Fischer titrator and ignited at 900℃ in a muffler roaster. The residuals of solvent were confirmed as ethyl ether by Headspace Gas Chromatography-Mass Spectrometry. The certified result with the mass balance method was 98.79% and the expanded uncertainty was 0.20% (k=2). The good homogeneity result in the 95% confidence interval was validated by F-test and t-test statistical methods with samples from 500 different bottles. The stability inspection was carried out on short-term (one month) and long-term (12 months) tests, and the results indicate that the stability period for 1,2,3,4-tetrachlorobenzene of storage is no less than 12 months at 20℃.